The Hurdles of Corporate Sustainability Claims A Case Study of Building Automation and Energy Savings - Gustavsson, Edvin; Zetterling, Knut (My University, 2026)
As the building sector contributes roughly 40% of global energy consumption, the twin transition of digitalization and green transformation has positioned building automation as a critical tool for decarbonization. However, hardware manufacturers face a significant challenge because current reporting standards, such as the GHG Protocol, fail to capture the potentially positive environmental impacts of "saved emissions" from the use of certain products. This creates a friction between the commercial need for organizational legitimacy in sustainability communication and the complex, non-linear reality of building physics, which can give rise to organized hypocrisy or greenwashing even where no deception is intended. This study employs an abductive research strategy and a case study of Bemsiq Group AB to explore these challenges. We used interviews, focus group discussions and a novel "white paper simulation" to document the specific frictions that arise when translating technical performance data into sustainability claims. The findings reveal that credible, aggregated sustainability disclosure has a hurdle in structural data gaps, such as the absence of standardized baselines and limited access to end-user operational data. Our "Friction Log" identifies conflicts between the frame of engineers prioritizing accuracy, and the business case frame of sales teams and management seeking cognitive clarity for customers. While the frictions are numerous, double-counting and attribution dilemmas are the main hurdles. To navigate these, we propose a shift toward a bottom-up strategy centered on micro-level validation through specific customer cases. This approach allows companies to secure legitimacy with verifiable evidence while advancing more transparent communication standards for the industry.
Keywords: Building Automation Control Systems (BACS); Twin transition; Energy performance gap; Organizational legitimacy; Scope 4 (saved emissions); Sustainability communication; Sensemaking; Boundary objects; Mimetic isomorphism